Minat Siswa Melanjutkan Studi Keperguruan Tinggi Ditinjau Dari Prestasi Belajar Dan Motivasi Belajar Pada Siswa Kelas XI SMA Negeri 1 Polanharjo Tahun Ajaran 2015/2016 - Wati, Istri; , Dr.Djalal Fuadi, MM (2017)
Istri Wati. A 210 110 161.A CONTINUING STUDY OF INTEREST EDUCATION VIEWED FROM HIGH ACHIEVEMENT MOTIVATION AND LEARNING IN CLASS XI SMA NEGERI 1 POLANHARJO ACADEMIC YEAR 2015/2016 Thesis. Pendididkan Accounting Studies Program Faculty of Teaching and Education University of Muhammadiyah Surakarta. January, 2017 The purpose of this study was to determine: 1) Effects of learning achievement against the interest of continued high education studies in class XI SMA N 1 Polanharjo the academic year 2015/2016. 2). Influence learning motivation against the interest of the students to continue their studies at the high education class XI student of SMAN 1 Polanharjo the academic year 2015/2016. 3). Effect of learning achievement and learning motivation to continue studies education high interest in class XI SMA N 1 Polanharjo the academic year 2015/2016. This study includes quantitative research. This study took place in SMA Negeri 1 Polanharjo. The technique of collecting data using questionnaires and documentation of student learning outcomes which have been tested by validity and reliability testing. The analysis technique used is multiple. To regression analysis regression equation; Y = 0,531 + 0,324X1 + 0,649X2, which means the result of high interest to continue education influenced by learning achievement and motivation to learn, based on the analysis and discussion can be concluded that: 1) .Prestasi learn positive effect on student interest high education continue their studies on high school students Negeri 1 Polanharjo force 2015/2016. It can be seen by the results of multiple linear regression analysis (t test) is known thitung>ttable, namely 2.713> 1.982 and the significance value <0.05, namely 0.008 with relative contributions of 12% and 88% effective contribution. 2). Motivation to learn positive effect on student interest continued high education at SMA Negeri 1 Polanharjo force 2015/2016. It can be seen by the results of multiple linear regression analysis (t test) is known thitung>ttable, namely 8.189> 1.982 and the significance value <0.05, namely 0.000 with the relative contribution of 5% and the effective contribution of 37.4%. 3) .Achievement learning and motivation to learn together positively to having an interest in the students continue their studies high education SMA force 2015/2016. It can be seen by the results of multiple linear regression analysis (F test) is known Fhitung>Ftable is 39.435> 3.081 with significance value <0.05 is 0.000. This shows that the interest of the students to continue their studies high education have the same tendency with the combination followed by an increase learning achievement and motivation to learn. The coefficient of determination of 42.4%, which means that there is influence exerted by variable combinations of learning achievement and learning motivation against the interest of the students to continue their studies education higher by 42.4%, while 57.6% are influenced by other factors not examined by the author.